1993
DOI: 10.1017/s0022215100122686
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapeutic effect on oropharyngeal flora in patients with head and neck cancer

Abstract: The affect of radiotherapy on oropharyngeal bacterial flora was studied in the hope that this might help in controlling post-operative infections in previously irradiated patients. Eighty patients were included from whom swabs were taken before and at the end of irradiation, Swabs were also taken two weeks after treatment in the last 40 patients. Thirty healthy controls were included.It was found that coagulase positive Staphylococcus aureus, β-haemolytic streptococci, Candida albicans, B. proteus, and Pseudom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 12 publications
(14 reference statements)
1
9
0
1
Order By: Relevance
“…To our knowledge this is the first study to characterize aerobic and facultatively anaerobic gram‐negative rods and cocci oral isolates from irradiated individuals suffering from solid tumors similar in nature and subjected to the same therapeutic irradiation protocol. A few reports are available on the increased oral colonization of aerobic and facultatively anaerobic gram‐negative rods and cocci in mucositis either during or immediately after irradiation therapy for what were usually a mixed collection of patients with various head and neck cancers ( 1, 16, 36). However only a few have investigated the delayed colonization patterns of these organisms in head and neck–irradiated individuals, particularly after resolution of irradiation‐induced mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge this is the first study to characterize aerobic and facultatively anaerobic gram‐negative rods and cocci oral isolates from irradiated individuals suffering from solid tumors similar in nature and subjected to the same therapeutic irradiation protocol. A few reports are available on the increased oral colonization of aerobic and facultatively anaerobic gram‐negative rods and cocci in mucositis either during or immediately after irradiation therapy for what were usually a mixed collection of patients with various head and neck cancers ( 1, 16, 36). However only a few have investigated the delayed colonization patterns of these organisms in head and neck–irradiated individuals, particularly after resolution of irradiation‐induced mucositis.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary abscesses due to MRSA have been described. 11 Irradiation itself has a significant effect on oropharyngeal flora, and Abu Shara et al 12 reported that Staphylococcus aureus may significantly increase after irradiation. Every effort should be made to ensure patients are rendered microbiologically 'sterile' prior to entering a transplant programme.…”
Section: Discussionmentioning
confidence: 99%
“…RT has been associated with the reduction of the blood supply to the irradiated areas, leading to a significant reduction of local immunity, redox potential of the tissues and delay of the wound repair, creating favorable conditions for the proliferation obligate anaerobes, such as genera Fusobacterium, Prevotella, Porphyromonas, and Treponema 23 , most of them considered putative periodontopathogens. In addition, radiation-induced xerostomia appears to affect the populations of anaerobic bacteria in oral cavity and exacerbate the prevalence and proportions of non-oral opportunistic pathogens, particularly staphylococci, enteric rods and cocci, as well pseudomonads in the oral biofilm from irradiated patients with adequate oral hygiene conditions 19,32,51,52 . However, only Gramnegative anaerobes producing black pigment (Porphyromonas spp.…”
Section: Mucositis Oral Bacterial Microbiota Enterobacteriaceae Andmentioning
confidence: 99%